Opinion of indian retailers on the impact of fdi policy amendments on the existing indian retail market: a selective study - Srikanth, Akondi (Journal of Management and Science, 2013)
This paper seeks to know the correspondence opinion of Indian retailers including traditional and organized retailers upon the impact of FDI policy amendments made by the Indian government on the Indian retail market. In methodology, purposive sampling technique was used for collecting 43 samples, out of which 32 samples had provided the data. The schedule had become a data collection tool whereas descriptive statistics and Mann –Whitney U test was used for analyzing the data. The results gave about 57.14% of organized retailers agreed in gaining employment opportunities by allowing FDI. From the survey, it was also found that 53.13% and 65.63% of all retailers had also agreed with the decrement in store profits and store sales respectively. In conclusion, the results found matching the perspective of traditional and organized retailers. With the direct opinion of retailers, only 37.5% have agreed and 62.5% have not agreed for allowing FDI. In limitation, the survey results are confined to an area in Hyderabad, Andhra Pradesh. In practice, this paper can bring to the awareness about FDI and its impact on the existing retailers that help them in building their competitive strategies to sustain and growth.